Sleep Quality Before And After Yoga Exercises In Elderly At Posyandu Lansia Yuswo Widodo Surabaya - Grace, Paulina H; Meryana, Pauline; Pantouw, Jakobus G (JOURNAL OF WIDYA MEDIKA JUNIOR, 2020)
Introduction: Population of the elderly in Indonesia continues to grow every year. Physiological setbacks that occur in the elderly contribute to the declining quality of sleep. Sleep disorder is one of the disorders in older people that are known to have a negative physical and psychological impact. One of the promotive actions to improve sleep quality in the elderly is physical activity, and one such activity that can be practiced by the elderly is yoga. Yoga has been shown to increase the quality of sleep in older people. Aim: The purpose of this research was to understand the difference in sleep quality before and after yoga exercise in the elderly at Posyandu Lansia Yuswo Widodo Surabaya. Method: This study was an analytical study with a pre-experimental design using one group pre-test post-test design, which was carried out for two months. The sampling method used was purposive sampling. The total samples obtained were 38 respondents, and all respondents were elderly in Posyandu Lansia Yuswo Widodo Surabaya. The research instrument used was the Pittsburgh Sleep Quality Index (PSQI). Statistical analysis used was the Wilcoxon Signed Rank Test. Result: The majority of respondents before yoga exercises had poor sleep quality, and the majority of respondents after yoga exercises had good sleep quality. The results showed that there was a significant difference between the quality of sleep before and after yoga in the elderly at the Posyandu Lansia Yuswo Widodo Surabaya (p = 0.000). Conclusion: The effective and routine application of yoga exercises could improve the quality of sleep in the elderly.